Global association of aerosol with flash density of intense lightning. (17th November 2017) - Altaratz, Orit; Kucienska, Beata; Kostinski, Alex; Raga, Graciela B; Koren, Ilan
Abstract: A global scale study of the association between aerosol loading and lightning production was conducted, using a full year's data for 2012 (as well as seasonal data) of the cloud-to-ground lightning record from the world wide lightning location network and aerosol optical depth measured by MODIS. 70% of all grid squares examined and 94% of the statistically significant ones had higher flash densities under polluted conditions than the clean ones. This trend is evident for large continental regions in North, Central and South America, Europe, southern Africa and north-east Australia. A detailed examination of the link to the meteorology was performed for four continental regions: the Amazon, North America, southern Africa and the Maritime Continent. The findings showed a similar trend under different meteorological conditions (defined by subsets of specified CAPE values and pressure velocity at 400 hPa). The results of this study suggest a route to association between aerosol loading and lightning-production rates in thunderclouds.